(untitled) (Web of Teachers: Inderscience Research, 2024)
In the second half of the twentieth century, English, Uzbek and Russian scholars have been interested in the linguistic and cultural analysis of the concept of hospitality. A lot of work has been done in the field of English. There are many theoretical literatures in this regard. Linguistic and cultural features of proverbs are also emphasized. In short, proverbs are one of the most studied areas.